Decidual γδT cells of early human pregnancy produce angiogenic and immunomodulatory proteins while also possessing cytotoxic potential - Nörenberg, Jasper; Vida, Péter; Bösmeier, Isabell; Forró, Barbara; Nörenberg, Anna; Buda, Ágnes; Simon, Diana; Erdő-Bonyár, Szabina; Jáksó, Pál; Kovács, Kálmán; Mikó, Éva; Berki, Tímea; et al. (Frontiers in Immunology, 2024)
During pregnancy, the maternal immune system must allow and support the growth of the developing placenta while maintaining the integrity of the mother's body. The trophoblast's unique HLA signature is a key factor in this physiological process. This study focuses on decidual γδT cell populations and examines their expression of receptors that bind to non-classical HLA molecules, HLA-E and HLA-G. We demonstrate that decidual γδT cell subsets, including Vδ1, Vδ2, and double-negative (DN) Vδ1-/Vδ2- cells express HLA-specific regulatory receptors, such as NKG2C, NKG2A, ILT2, and KIR2DL4, each with varying dominance. Furthermore, decidual γδT cells produce cytokines (G-CSF, FGF2) and cytotoxic mediators (Granulysin, IFN-γ), suggesting functions in placental growth and pathogen defense. However, these processes seem to be controlled by factors other than trophoblast-derived non-classical HLA molecules. These findings indicate that decidual γδT cells have the potential to actively contribute to the maintenance of healthy human pregnancy.